Catechin and quercetin attenuate adipose inflammation in fructose-fed rats and in 3T3-L1 adipocytes - Vazquez Prieto, Marcela A. (Mol Nutr Food Res, 2015)
SCOPE: This study evaluated the capacity of dietary catechin (C), quercetin (Q) and the combination of both (CQ), to attenuate adipose inflammation triggered by high fructose (HFr) consumption in rats and by tumor necrosis factor alpha (TNFα) in 3T3-L1 adipocytes. METHODS AND RESULTS: In rats, HFr consumption for 6 wk caused dyslipidemia, insulin resistance, reduced plasma adiponectin, adiposity, and adipose tissue inflammation. Dietary supplementation with 20 mg/kg/d of C, Q and CQ improved all these parameters. In 3T3-L1 adipocytes, C and Q attenuated TNFα-induced elevated protein carbonyls, increased pro-inflammatory cytokine expression (MCP-1, resistin), and decreased adiponectin. The protective effects of C and Q on adipose inflammation are in part associated with their capacity to: i) decrease the activation of the mitogen activated kinases (MAPKs) JNK and p38; and ii) prevent the downregulation of PPARγ. In summary, C and Q, and to a larger extent the combination of both, attenuated adipose pro-inflammatory signaling cascades and regulated the balance of molecules that improve (adiponectin) or impair (TNFα, MCP-1, resistin) insulin sensitivity. CONCLUSION: Together, these findings suggest that dietary Q and C may have potential benefits in mitigating MetS associated adipose inflammation, oxidative stress, and insulin resistance.